PERANCANGAN KONSEP TEMPAT TIDUR RUMAH SAKIT MEMPERTIMBANGKAN PROSES PEMINDAHAN PASIEN (STUDI KASUS: RUMAH SAKIT ”ZZZ” DI SURAKARTA) - Rahmaniyah Dwi Astuti; Ilham Priadythama Ilham Priadythama; Nanung Eko Setyawan (Prosiding SNST Fakultas Teknik, 2012)
Manual patient bed transfer is still bringing in a problem for nurses and also for patients when the nursing moves from or to wards in hospital, especially in a nursing with surgery. For the nurses, it can lead to low back pain because they must bow when they lift and move the patient body. For the patients, the transfer process can definitely cause body movement which can cause inconvenience, for example for a patient with a physical trauma. Therefore, it would be very helpfull if there is something which can change the traditional technique of patient transfer. The objective of this study is to design a concept of interchangeable hospital bed mattresses.The first step of this study is the problem analysis to the patient transfer process and the beds they currently use. This activity was begins trough observation, direct interrogation, and the deployment of Nordic Body Map equiped questionaire. After the analysis showed the ponits of the problem, there can be developed a bed design concepts with their fitures which can accommodate requirements of the process, encompass the nurses’ anthropometry based bed dimension, the bed mechanical mechanisms, and some supporting fitures. The result of this study are concepts of both hospital wards bed and transit bed which theoretically can eliminate the nurses low back pain. The transfer is enabled with interchangeable mattress slide mechanisms with remote locks to ensure the effectivity and the safety of the process. The transit bed is designed with light costruction and remote brake equiped handle to increase its mobility and handling. Kata kunci : nurse, design, manual patient bed transfer.